Students’ Grammatical Error in Writing Narrative Text - Yusni Sinaga; Putri Ramadhani (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2020)
Students made errors in writing narrative text. Two reasons why students made errors because less in grammar mastery and confuses to differenciate of the verb. This writing is to find out the grammatical errors. The method of research is descriptive quantitative. Process of data are analyzed by reading students’ writing firstly, identification, classification, tabulating, describing, and taking conclusion about the errors. After analyzing the data, it found that students made errors in omission, addition, misformation, and misordering categories. The highest frequency of item error was in using verb tense with total of 61 errors. Meanwhile, the lowest frequency of item errors were in using adverb and adjective with total of 6 errors. Total of the errors was 204.